Factorial structure of the patient health questionnaire-9, generalized anxiety disorder-7 and berger HIV stigma scale-short form among adolescents living with HIV in Ghana. - Samuel Adjorlolo; Dorothy Serwaa Boakye (PLoS ONE)
Background Mental health issues and stigma experiences significantly affect adolescents living with HIV (ALHIV). While the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Berger HIV Stigma Scale-Short Form (HSS-SF) are widely used screening tools for mental health and stigma, their factorial validity among ALHIV in resource-limited settings such as Ghana remains understudied. This study investigated the factor structure, internal consistency, and correlations of the PHQ-9, GAD-7, and HSS-SF among ALHIV in Ghana. Methods A cross-sectional study was conducted among 105 ALHIV (aged 10-24 years) receiving care at three government hospitals in Eastern Ghana. Confirmatory factor analyses were conducted to examine the factor structure of the PHQ-9 and GAD-7 and HSS-SF. Results A two-factor structure showed the best fit for PHQ-9, with satisfactory internal consistency for cognitive/affective (α = 0.79) and somatic factors (α = 0.70). The GAD-7 demonstrated best fit as a unidimensional factor structure, with acceptable internal consistency (α = 0.88). The HSS-SF was found to be best represented by a three-factor structure, with internal consistency ranging from 0.76 to 0.95 across subscales. Conclusions The PHQ-9, GAD-7, and HSS-SF demonstrated acceptable factorial structure and internal consistency among Ghanaian ALHIV, supporting their utility as screening tools in this population.